2012
DOI: 10.1007/s10584-012-0561-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on sugarcane attainable yield in southern Brazil

Abstract: This study evaluated the effects of climate change on sugarcane yield, water use efficiency, and irrigation needs in southern Brazil, based on downscaled outputs of two general circulation models (PRECIS and CSIRO) and a sugarcane growth model. For three harvest cycles every year, the DSSAT/CANEGRO model was used to simulate the baseline and four future climate scenarios for stalk yield for the 2050s. The model was calibrated for the main cultivar currently grown in Brazil based on five field experiments under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 31 publications
5
70
1
17
Order By: Relevance
“…Both Table 3 and Figure 5 show variation (uncertainty) in future arising from differences in GCM projections. Simulated cane yields increased under all future scenarios, at all sites; this is consistent with the findings of Knox et al (2010), Marin et al (2012), Schulze and Kunz (2010) and Singels et al (2013). The relative increases were greatest at La Mercy (irrigated: 14 %; rainfed: 15 %), and smallest at Malelane (11 %).…”
Section: Weather Datasupporting
confidence: 86%
See 1 more Smart Citation
“…Both Table 3 and Figure 5 show variation (uncertainty) in future arising from differences in GCM projections. Simulated cane yields increased under all future scenarios, at all sites; this is consistent with the findings of Knox et al (2010), Marin et al (2012), Schulze and Kunz (2010) and Singels et al (2013). The relative increases were greatest at La Mercy (irrigated: 14 %; rainfed: 15 %), and smallest at Malelane (11 %).…”
Section: Weather Datasupporting
confidence: 86%
“…Rainfed sugarcane yield increases of 15 to 40 t/ha to intermediate future (2050s) climate were also reported by Schulze and Kunz (2010) for South Africa. Marin et al (2012) reported a 24% increase in rainfed sugarcane yields, and a 34% increase in water use efficiency in south-eastern Brazil (2100s). Singels et al (2013) reported increases in future (2100s) crop water use of 1 to 8%, and cane yield increases of 4 to 20% for sites in SA, Australia and Brazil (2100s), while sucrose yield responses varied widely (between -33% and +13%).…”
Section: Introductionmentioning
confidence: 99%
“…This latter sugarcane producing region presents the highest changes to drier conditions among all locations. This remarkable regional intensification on drought occurrence is of particular concern because, as other locations of the State of São Paulo (Marin et al 2013), the sugarcane production in Ribeirão Preto is heavily based on rainfed systems. The frequency analysis performed at 2-month time scales leads to equivalent results as those exemplified in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Means followed by the same letter in each location do not differ by at 5% probability. enhance productivity of cotton species G. hirsutum and G. barbadense, in the last 50 years, most breeding programs have focused on increases in the net rate of photosynthesis and tolerance to elevated temperatures by increasing stomatal conductance (Radin et al, 1994;Lu et al, 1998;Zhang et al, 2013). However, from a global warm perspective (Trenberth et al, 2007;Cuadra et al, 2012;Marin et al, 2013;Bowman et al, 2013), breeding programs should redirect their efforts to construct more suitable plants to face challenges in new climate scenarios. In this view, plant breeders and physiologists are concentrating their efforts in the construction of plants not only to survive under abiotic stresses but also to be stable and productive in these hard environments.…”
Section: Resultsmentioning
confidence: 99%